The Capability of Consortium Phosphate Solubilizing Bacteria and IAA Producing Fungi on Promoting Elephant Grass Growth - Witiyasti Imaningsih; Anang Kadarsah; Raden Dwi Thriwantho Rusmannurrachmad (Jurnal Biodjati, 2019)
Phosphorus compound in the critical land is relatively low that caused phosphorus is bonded to metals. The isolate BRC-AP and BRC-AK are a phosphate solubilizing bacteria (PSB) indigenous critical land that has the ability to dissolve phosphate. The used of phosphate solubilizing bacteria are able to improve plant growth on critical lands. The aimed of this study was to measure the growth rate of shoot length, root length and biomass of root, and leaf cuttings elephant grass (Pennisetum purpureum cv. King Grass) which inocu-lated with the consortium of phosphate solubilizing bacteria and IAA producing mold. Phosphate dissolving activity is determined by the formation of clear zone in solid Pikovskaya medium, synergism assay between bacteria and fungi observed on SDA medium then proceed testing the ability of bacteria and fungi consortium to promote plant growth. The result showed that the highest of phosphate solubility in-dex was found in isolate BRC-AP (27), addition of the combination of isolate BRC-AP, BRC-AK and Humicola sp. R.Dn have significant effect on shoot growth in the first week and leaf dry weight. The high-est length shoot of cutting elephant grass was found in treatment with the consortium of phosphate solubilizing bacteria and IAA producing mold (BRC-AP + BRC-AK + KP) (58.66 cm). The highest of leaf dry weight was found in treatment with BRC-AP + BRC-AK + KP (5.65 gr). The addition of consortium phosphate solubilizing bacteria and IAA producing fungi from South Kalimantan critical land proved can improve plant growth especially length shoot and leaf dry weight.